2020
DOI: 10.2174/1389557520666200624193300
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fungi in the Fight Against Neglected Tropical Diseases

Abstract: : Neglected tropical diseases are a serious global public health problem and they are one of the main causes of mortality and morbidity, especially in underdeveloped countries. These diseases have several implications for health and they are considered a priority in global eradication programs for disease control. The aim of this mini-review is to report recent studies on the fight against neglected diseases, namely dengue fever, chikungunya, zika, malaria protozoa, Chagas disease, leishmaniasis, schistosomias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Owing to the resistance of mosquitoes and the low effectiveness and high cost of programs to control the vectors of these diseases [8][9][10] , new strategies are needed to combat vectors using mechanisms that are less polluting, less toxic, and pose less risk to human health 11,12 . Some studies involving natural bioactive products made from endophytic fungi have revealed promising alternatives 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the resistance of mosquitoes and the low effectiveness and high cost of programs to control the vectors of these diseases [8][9][10] , new strategies are needed to combat vectors using mechanisms that are less polluting, less toxic, and pose less risk to human health 11,12 . Some studies involving natural bioactive products made from endophytic fungi have revealed promising alternatives 13 .…”
Section: Introductionmentioning
confidence: 99%